Changing Fisheries: How Cutting-Edge Technology Affects Sustainable Aquaculture - Jean L. Son (Advances in Aquaculture and Fisheries Management, 2025)
This article explores how modern technology is changing fisheries, concentrating mostly on how it affects sustainable aquaculture. The industry has entered a new phase with the integration of cutting-edge technology including automation, precision fishing, sustainable aquaculture techniques, data analytics, machine learning, and smart fishing gear. In addition to increasing productivity and efficiency, these advances are essential in tackling the urgent problems of overfishing, environmental damage, and seafood traceability. The article examines the various ways that technology is being used in fisheries, highlighting the possibility of a more ethical, transparent, and sustainable aquaculture industry in the future. But it also emphasizes how important it is to confront issues and moral dilemmas in order to guarantee a responsible and fair response to the rapidly evolving field of fishing technology.